Clinical Application of the SADL Scale in Private Practice II: Predictive Validity of Fitting Variables - Hosford-Dunn, Holly; Halpern, Jerry (Journal of the American Academy of Audiology, 2001)
Predictive validity of 44 independent variables and their interactions with Satisfaction with Amplification in Daily Life (SADL) scores was assessed. SADL scores were influenced by patient age, years of hearing aid experience, hours of use per day, perceived hearing difficulty, pure-tone average, hearing aid style, processor type, and manufacturer's invoice cost. The relative importance of these variables to SADL measures was complex and very small, but the variables and their squares and interactions improved r2 predictions of SADL Global and subscale scores in a separate stepwise multiple linear regression procedure by 12 to 33 percent compared to SADL norms alone. More research with additional variables is needed to develop a clinically useful model for predicting wearer satisfaction. Clinically, SADL scores yield subscale-specific patterns of satisfaction and dissatisfaction that help in intervention planning and serve as graphic "snapshots" of satisfaction status. A series of patient profiles are presented illustrating the potential usefulness of the SADL in predicting hearing aid satisfaction. With its good construct and psychometric properties, the SADL could serve as a gold standard for satisfaction outcomes and a basis for development of a predictive model of hearing aid fitting success.Abbreviations: ANOVA = analysis of variance, BTE = behind the ear, CIC = completely in the canal, DSP = digital signal processing, ITC = in the canal, ITE = in the ear, PP-SADL = private practice SADL group, PTA = pure-tone average, SADL = Satisfaction with Amplification in Daily Life
Keywords: Hearing aids; outcome; satisfaction; Satisfaction with Amplification in Daily Life; validity